2019
DOI: 10.1038/s41419-019-1823-7
|View full text |Cite
|
Sign up to set email alerts
|

O-cyclic phytosphingosine-1-phosphate stimulates HIF1α-dependent glycolytic reprogramming to enhance the therapeutic potential of mesenchymal stem cells

Abstract: O-cyclic phytosphingosine-1-phosphate (cP1P) is a novel chemically synthesized sphingosine metabolite derived from phytosphingosine-1-phosphate. Although structurally similar to sphingosine-1-phosphate (S1P), its biological properties in stem cells remain to be reported. We investigated the effect of cP1P on the therapeutic potential of mesenchymal stem cells (MSCs) and their regulatory mechanism. We found that, under hypoxia, cP1P suppressed MSC mitochondrial dysfunction and apoptosis. Metabolic data revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 79 publications
5
15
0
Order By: Relevance
“…All the effects of FP on glycolysis were mediated through its interaction with S1P1 receptors, as all of these effects disappeared when the S1P1 antagonist was present, being affected the basal glycolysis, glycolytic capacity, glycolytic reserve, and the capacity to maintain the aldolase activity. This finding was common with other authors who also found the need of interaction of FP with its receptor to develop its glycolytic protective actions [ 54 , 60 ]. In the study of G-6-PDH activity, the effect of FP was also mediated by the interaction with its specific S1P1 receptor, as the increase in G-6-PDH activity was totally abolished when the S1P1 antagonist was present in the incubation media.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…All the effects of FP on glycolysis were mediated through its interaction with S1P1 receptors, as all of these effects disappeared when the S1P1 antagonist was present, being affected the basal glycolysis, glycolytic capacity, glycolytic reserve, and the capacity to maintain the aldolase activity. This finding was common with other authors who also found the need of interaction of FP with its receptor to develop its glycolytic protective actions [ 54 , 60 ]. In the study of G-6-PDH activity, the effect of FP was also mediated by the interaction with its specific S1P1 receptor, as the increase in G-6-PDH activity was totally abolished when the S1P1 antagonist was present in the incubation media.…”
Section: Resultssupporting
confidence: 88%
“…When we studied the glycolytic reserve, which is the ability of cells to adapt to extra energetic demands when the glycolytic function is working at maximum, neurons incubated in presence of VitK3 also showed a reduction in glycolytic reserve by 48% compared to the control; again, coincubation in the presence of FP reverted this value to control levels (Figure 2a,d). Our results partially agree with those from Lee et al [54], who found an increase of glycolytic capacity with S1P mimetics in mesenchymal cells, although the authors did not find differences in glycolytic reserve, possibly due to the different type of cells. This recovery in glycolytic capacity would rapidly supply ATP in situations where it is needed and when the mitochondrial metabolism, although generally having a high capacity to produce ATP, is not totally functional, as demonstrated previously.…”
Section: Glucose Metabolism Studiessupporting
confidence: 92%
See 2 more Smart Citations
“…Zhang et al investigated the use of MSCs in myocardial infarction and showed that pre-treating MSCs with asprosin, an adipokine that inhibits reactive oxygen species (ROS) generation, significantly improved MSC homing and proliferation while reducing apoptosis and scar size [98]. Lee et al also demonstrated the effectiveness of pre-treatment with O-cyclic-phytosphingosine-1-phosphate which, through reversal of ROS damage, upregulated proliferation, migration and anti-apoptosis [99]. These studies propose innovative ways of rejuvenating autologous MSCs for the treatment of atherosclerosis.…”
Section: Considerations For Therapeutic Efficacymentioning
confidence: 99%